Digitalization of maintenance record-keeping for automation and telemechanics devices at railway stations (Международный научный журнал «Инженер», 2026)
The article addresses the issues associated with the manual method of recording maintenance for automation, signaling, and telemechanics devices at railway stations in Uzbekistan. It analyzes the current practice of maintaining paper documentation and identifies major shortcomings, including high labor intensity, input errors, delays, and lack of transparency. A digital record-keeping model is proposed, which includes a workflow algorithm, registration and analytics modules, as well as integration with maintenance schedules. The practical importance of transitioning to an automated system is substantiated. The expected outcomes include increased reliability, cost reduction, and improved management of technical processes.